The Value of Local Spirituality in Indonesian Society as the Basis for Managing Religious Ecotourism - Achmad Fathor Rosyid; Ahidul Asror; Zaki Al-Mubarok; Harapandi Dahri (Mahkota Science Publishers, 2025)
Amidst the global ecological crisis, the strengthening of identity politics, and the increasing commodification of religion, local spirituality values form the basis for the management of religious ecotourism. The aim is to develop a conceptual framework that centres local spirituality in religious ecotourism management. This study is positioned as a conceptual study, employing an integrative literature review to compile and critique previous theories and findings systematically. The results conclude that truly sustainable religious ecotourism requires a radical shift from tourism that merely uses local spirituality to governance led by local spirituality as a source of values, direction, and ethical boundaries. The conflict between the sacredness of space and commercialisation can only be resolved if concepts such as Tri Hita Karana, Siri'na Pacce, Sedulur Papat Lima Pancer, and Huma Betang are operated as a framework for decision-making, and if religious rituals are transformed from routine ceremonies into vehicles for education and mobilisation of collective ecological awareness. Thus, religious ecotourism is no longer another face of a sanctified extractive industry, but a concrete path towards Indonesian eco-theology, a practice of faith that binds communities to protect the earth, honour their ancestors, and redefine the meaning of progress in the midst of an ecological crisis.